Decoupling of forest water supply and agricultural water demand attributable to deforestation in North Korea. (15th October 2019) - Lim, Chul-Hee; Song, Cholho; Choi, Yuyoung; Jeon, Seong Woo; Lee, Woo-Kyun
Abstract: This study focused on changes in water balance attributable to severe deforestation in North Korea. The forest water supply and agricultural water demand of North Korea were quantified to identify their decoupling over the past three decades. Forest water supply and agricultural water demand before and after deforestation were estimated using the InVEST-WY (Integrated Valuation of Ecosystem Services and Trade-offs – Water Yield) and EPIC (Environmental Policy Integrated Climate) models, respectively. Analysis of land cover change before and after deforestation showed that area under forests decreased by 25%, whereas that under cropland increased by 63%, and that the conversion from forest to cropland was the largest for the study period. As a result, agricultural water demand increased and forest water supply decreased, significantly. Analysis of the net impact of deforestation on water budgets using recent climate and two land covers showed that forest water supply decreased by 43% and agricultural water demand increased by 62%. An assessment of the water balance at the watershed level showed that the Taedong, Ryesong, and Tumen Rivers suffered the largest negative change in terms of the large gross impact of deforestation on water resources. The water balance of the entire North Korea has declined by 51% and this is attributable to deforestation. In contrast, South Korea has experienced success in national-scale afforestation in recent decades, and North Korea can emulate this. The restoration of forests in North Korea promises more than environmental benefits; it will provide a new growth engine for the prosperity of the Korean Peninsula as a whole. Highlights: North Korea's land cover changes before (1980s) and after (2010s) deforestation showed that forests decreased by 25%, cropland increased by 63%. Estimating net impact of deforestation using InVEST and EPIC model, indicated that forest water supply decreased by 43% and agricultural water demand increased by 62%. The water balance of entire North Korea which was 32, 406 million m 3 yr −1 before deforestation, was declined by 51% to 16, 015 million m 3 yr −1 after deforestation. Attributable to deforestation, regions that supply water transformed into high demand areas, accelerating negative changes in the national water balance.